Sistem Pendukung Keputusan Pembagian Kelas Unggulan Siswa Baru Menggunakan Metode Promethee Pada STM Raksana Medan - Junaidi (JUKI : Jurnal Komputer dan Informatika, 2021)
Education has a very decisive role, not only for the development and manifestation of individuals but also for the development of a nation and a state. The progress of a culture depends on how that culture recognizes, appreciates, and uses its human resources. This is closely related to the quality of education provided to members of the community. The word decision means choice, namely the choice of two or more possibilities. Decision making is hardly a choice between right and wrong but what often happens is a choice between "almost right" and "maybe wrong". Decision making in an organization is the result of a continuous process of communication and participation from the entire organization. The results of these decisions can be statements that are agreed between alternatives or between procedures to achieve certain goals. However, to be able to determine the best decision, there are several methods that can be used to build a decision support system, one of which is Promethee. The promethee method is included in the Multi Criteria Decision Making (MCDM) group solving or multiple criteria decision making which is a discipline that is very important in making decisions on a problem that has more than one criterion (multicriteria).